The impact of audit and governance committee on internal shariah audit performance: an islamic-worldview based - Azam Abdelhakeem Khalid (Tanjong Malim, 2019)
The impact of audit and governance committee on internal shariah audit performance: an islamic-worldview based by Azam Abdelhakeem Khalid